EXPLORING THE “SARDOBA” THEME IN UZBEK HISTORICAL PAINTING: COMPOSITION, SYMBOLISM, AND ARTISTIC TECHNIQUES - Davlatova Nilufar Mansurovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article examines the depiction of the “Sardoba” theme in Uzbek historical painting, focusing on compositional strategies, symbolic representation, and artistic techniques. The study highlights how Uzbek artists balance historical accuracy with creative expression to convey cultural heritage and communal significance. Analysis of selected artworks demonstrates the role of color, perspective, light, and human activity in narrative construction. The research underscores the importance of teaching historical composition in art education and preserving cultural identity through visual storytelling.